Liderança e gênero na administração pública: a percepção dos gerentes das agências da previdência social em Recife - Andrade, Leozina Barbosa de (2012)
The challenges posed by the redefinition of the rol e of the State and the quest for efficiency in the provision of public services underlie the reali zation of this study. Therefore, we addressed the reality of the managers of the Social Security National Institute of Social Insurance (INSS in Portuguese), key persons in implementing a model of Public Administration that meets social demands. It was sought to identify the perce ptions of leadership development, explaining gender relations experienced in the exer cise of these positions. A gender approach was based on the significant number of women existi ng in public service. Thus, it is understood that the issues of leadership in this se ctor are permeated by gender relations. In this aspect, we performed a trajectory and contextu alization of women's struggles for emancipation and their situation in prominent posit ions in the public service. Contextualizing the present study, we carried out the historical co nstruction and presentation of concepts related to modernization of the state, the Public M anagement and the provision of public services in Brazil, that led to the discussion of t opics related to citizenship and social rights. Regarding methodological aspects, this is a case st udy with a qualitative approach and descriptive character. The fieldwork provided means for data fetching with the use of questionnaire and semi structured interview associa ted with the drawings construction. We adopted the content analysis for the data treatment . Was performed to characterize the socio- professional integration of servers occupying manag ement positions at the operational level of the INSS and addressed the dilemmas arising from th e exercise of management positions and the quest for leadership in developing the skills n ecessary for the management of the agencies. In the context of gender relations, were correlated meanings, from the elaboration of experiences, while men and women in the role of man ager performance in these workplaces. Important results were observed in the analysis of interviews with the technique of building designs. In general, managers demonstrated enjoy an d be proud of what they do, however, there is wear and tensions arising from the deficie ncies of infrastructure, among others. Nevertheless, managers demonstrate ability to learn and excel in these situations many positive feelings among them, involvement, commitme nt and collaboration. The survey results raise questions and recommendations that wi ll be made available to the organization, and elements with reflections in order to contribut e to the educational processes in people management.